In-plane crashworthiness of re-entrant hierarchical honeycombs with negative Poisson's ratio. (1st December 2019) - Tan, H.L.; He, Z.C.; Li, K.X.; Li, Eric; Cheng, A.G.; Xu, Bing
Abstract: Both auxetic structures and hierarchical honeycombs are marked with lightweight and excellent mechanical properties. Here, we combine the characteristics of auxetic structures and hierarchical honeycombs, and propose two re-entrant hierarchical honeycombs constructed by replacing the cell walls of re-entrant honeycombs with regular hexagon substructure (RHH) and equilateral triangle substructure (RHT). The honeycombs are subjected to in-plane impact in order to investigate the crashworthiness by using the commercial software LS-DYNA. The plateau stress of RHH and RHT in x and y directions are derived by a two-scale method. The results from numerical simulation indicate that the specific energy absorption of RHT and RHH is improved by up to 292% and 105%. RHT and RHH improve the mean crushing force value by 298%, 108% respectively compared with the classic re-entrant honeycomb (RH) under quasi-static loading at stress plateau region. The RHT and RHH still have the characteristic of negative Poisson's ratio. Additionally, the parametric studies are further carried out to investigate the effects of impact velocities and relative densities on crashworthiness. All the findings of this study indicate that the proposed two hierarchical honeycombs exhibit an improved crushing performance, and RHT provides the highest energy absorption capacity among all specimens.